Social protection in times of conflict: Evidence from Ethiopia - Rute Martins Caeiro; Rachel Sabates-Wheeler; Patricia Justino (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2025)
This paper examines the role of social protection in mitigating the adverse effects of conflict on household welfare. We assess the impact of a graduation intervention linked to Ethiopia's Productive Safety Net Programme, focusing on Amhara, a region severely affected by the Tigray conflict. Using data from a large randomized controlled trial and panel surveys conducted before and after the conflict, we evaluate the effectiveness of social protection in conflict settings. Our estimation strategy leverages variation in conflict exposure combined with exogenous programme participation. We find that conflict significantly reduces food expenditures, but social protection mitigates this effect, leading to improved food security and lower poverty rates among beneficiaries compared to non-beneficiaries. However, we find no impact on asset accumulation. These findings underscore the role of social protection in shielding vulnerable households from conflict's worst effects while highlighting its limitations in fostering long-term resilience.
Keywords: O12; I38; F51; C93; 330; conflict; social protection; safety net programme; poverty; Ethiopia